2017
DOI: 10.1002/pro.3292
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of nearest neighbor effects on backbone torsion angles and NMR scalar coupling constants in disordered proteins

Abstract: Using fine-tuned hydrogen bonding criteria, a library of coiled peptide fragments has been generated from a large set of high-resolution protein X-ray structures. This library is shown to be an improved representation of ϕ/ψ torsion angles seen in intrinsically disordered proteins (IDPs). The ϕ/ψ torsion angle distribution of the library, on average, provides good agreement with experimentally observed chemical shifts and J coupling constants for a set of five disordered proteins. Inspection of the coil librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…However, measurements of the 3 J HNHA coupling constants over a pH range from 4.0 to 8.0 showed that those of the phosphorylated serine and threonine, but not those of the tyrosine or the glutamines, were pH dependent. At low pH, the 3 J HNHA coupling constants had random coil values (Shen et al 2018), but decreased and reached 4.7 Hz (pSer) and 4.0 Hz (pThr), respectively, at pH 8.0 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 87%
“…However, measurements of the 3 J HNHA coupling constants over a pH range from 4.0 to 8.0 showed that those of the phosphorylated serine and threonine, but not those of the tyrosine or the glutamines, were pH dependent. At low pH, the 3 J HNHA coupling constants had random coil values (Shen et al 2018), but decreased and reached 4.7 Hz (pSer) and 4.0 Hz (pThr), respectively, at pH 8.0 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 87%
“…fig.1); this led us to adopt a standard deviaVon normalisaVon for the observed torsional angles. While several different normalisaVon approaches exist for dihedral angles [30], [31], the mathemaVcal techniques directly depend on the parameter incorporaVon into further equaVons which, in our case, needed to be formulated in a way to preserve Ramachandran plot direcVonality based on posiVve and negaVve value so that mulVplicaVon operaVon allowed to predict either β-sheet/strand type of conformaVon (negaVve) or α-helix (posiVve) for the most predominant secondary structure elements (supl. fig.1).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The increasing frequency of information exchange has been prompted to transfer from old information transmission mod to more convenient transmission mod. With the rapid development of computer and network, network transmission has been highly paid attention [1]. The text, image, video data and other information involved in transmission are insignificant, and some are related to state secrets, trade secrets or personal privacy.…”
Section: Introductionmentioning
confidence: 99%